2022
DOI: 10.1042/bcj20210724
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of TNF-independent RIPK3-mediated cell death

Abstract: Apoptosis and necroptosis regulate many aspects of organismal biology and are involved in various human diseases. TNF is well known to induce both of these forms of cell death and the underlying mechanisms have been elaborately described. However, cells can also engage apoptosis and necroptosis through TNF-independent mechanisms, involving, for example, activation of the pattern recognition receptors Toll-like receptor (TLR)-3 and -4, or zDNA-binding protein 1 (ZBP1). In this context, cell death signaling depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 139 publications
0
4
1
Order By: Relevance
“…It is known that RIPK1 can interact with RIPK3 through the RHIM domain and trigger auto‐ and transphosphorylation of RIPK3 41 . It has been demonstrated that activated RIPK3 can induce both necroptosis and apoptosis, 42 although, in our system, RIPK3 inhibition did not alter cell response to 5‐FU or OxaPt.…”
Section: Discussioncontrasting
confidence: 58%
“…It is known that RIPK1 can interact with RIPK3 through the RHIM domain and trigger auto‐ and transphosphorylation of RIPK3 41 . It has been demonstrated that activated RIPK3 can induce both necroptosis and apoptosis, 42 although, in our system, RIPK3 inhibition did not alter cell response to 5‐FU or OxaPt.…”
Section: Discussioncontrasting
confidence: 58%
“…Like apoptosis, PKR-mediated necroptosis can occur in response to IFNs, possibly requiring PKR interaction with RIPK1 [ 113 ]. While other groups have also observed a physical association between PKR and RIPK1 [ 143 ], the exact role that PKR plays in initiating necroptosis in response to IFN stimulation remains unclear [ 144 ]. Notably it has been proposed that IFN-stimulated PKR-mediated necroptosis is restricted to the G2M stage of the cell cycle, when FADD is disabled, preventing capase-8 inhibition of necrosome formation [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…While unexpected, such a response could be important against severe pathogens that disarm RhoA, the key upstream activator of ROCK1, since it could enable B cells to recruit and organize an inflammatory infiltrate and "jump-start" responses during these infections. Surprisingly, the enhanced proinflammatory capabilities of ROCK1-deficient B cells were accompanied by the dysregulated assembly of p62 complexes containing key ripoptosome components, ZBP1, RIPK1, and RIPK3, long implicated in the orchestration of inflammatory responses and necroptosis in innate cells 52 but whose role in B cells is largely unexplored.…”
Section: Discussionmentioning
confidence: 99%